Effects of concentrate mixture level on nutrient digestibility, growth, production and reproduction performance of Jamunapari goat under semi intensive condition (Research in Agriculture Livestock and Fisheries, 2021)
Twenty female Jamunapari goats of live weight of 10.5 ± 1.2 kg at 08± 0.56 months of age were used for 240 days feeding trial. Goats were assigned to four dietary treatments in a completely randomized design with five (05) goats in each group. All animals were supplied ad libitum green grass and water. They were supplied 150, 200, 250, 300 gm concentrate mixture per day with roughage for group T1, T2, T3, and T4 respectively. Total dry matter (TDM) intake (413.2, 456.67, 489.2 and 495.7g/day) in groups T1, T2, T3, and T4, respectively, was significantly (p≤0.01) influenced by the level of concentrate in the diet. Average total digestible crude protein (DCP) intake (3.1, 3.5, 3.9, 4.0 g/kg body weight and average total digestible nutrient (TDN) intake 21.1, 22.3, 24.7, 25.1 g/kg body weight was significantly (p≤0.01) higher in group T4 and lower in group T1. The nutrient intake and digestibility were also significantly higher (p≤0.01) in T4 group. The percent digestibility of dry matter (DM), organic matter (OM), crude protein (CP), crude fiber (CF), ether extract (EE) and nitrogen free extract (NFE) were 70.1, 75.99, 73.50, 67.24, 62.13 and 49.60%, 73.14, 76.97,76.84, 68.32, 64.04 and 53.25%, 75.45,78.44,78.67,70.43,68.43 and 59.77%, 79.56, 80.16,81.69,72.45,70.82 and 63.09% in T1, T2, T3 and T4 group, respectively. Reproductive performances, birth weight of kids and litter size did not differ significantly between groups, but had significant effect on feed digestibility and milk production. Daily 300 gm concentrate mixture along with roughage is necessary for better growth, production and reproduction performance of Jamunapari doe in semi-intensive system.Res. Agric., Livest. Fish.8(2): 223-230, August 2021